PENERAPAN PEMBELAJARAN BIOTEKNOLOGI MELALUI FERMENTASI UMBI-UMBIAN MENJADI PRODUK TAPE SEBAGAI SUBSTITUSI PANGAN BERAS - Suanda, I Wayan; Sumarya, I Made (Widyadari: Jurnal Pendidikan, 2019)
This research aims to use tubers into tape products as a substitution for rice in the application of fermented biotechnological learning. The research used a type of local tubers such as sweet potato, which includes purple sweet potato (purple color), honey sweet potato (yellow color), white sweet potato (white color) and taro (Colocasia esculenta (L.) Schott.), while the control treatment used cassava (Manihot utillisima Crantz) using completely randomized research design. The tests were conducted by looking for the alcohol content and through organoleptic test (taste) as well as the appearance of the tape products by involving 20 researchers as testers. The results showed that the making of tape using tubers through fermentation process produced an average alcohol of 3.994% in honey sweet potatoes; 1.3773% in white sweet potato; 1.0576% in purple sweet potato; 1.3295% in taro and 0.59625% in cassava. The organoleptic test conducted by the panelists showed: honey sweet potato (yellow color, soft texture, sour taste, alcoholic aroma, attractive appearance); white sweet potato (white color, soft texture, sour taste, alcoholic aroma, attractive appearance); purple sweet potato (purple color, soft texture, sour taste, alcoholic aroma, attractive appearance); taro (whitecolor, rather dense texture, sour taste, mildly alcoholic aroma, ordinary appearance) and cassava (yellow color, soft texture, sour taste, alcoholic aroma, attractive appearance).